Emic definitions of empowerment for just development: learnings from Kenya - Zaremba, Haley; Nchanji, Eileen Bogweh; Guettou-Djurfeldt, Nadia; North, Hanna; Slavchevska, Vanya; Macchioni Giaquinto, Annarita (BioMed Central, 2024)
This mixed-methods study examines how men and women of different ages engaged in agriculture in Kilifi and Kiambu counties in Kenya define empowerment and describe empowerment pathways, and how empowered people are perceived by their families and communities. It also examines how emic understandings of empowerment—definitions which originate from within a given cultural context—compare to quantitative empowerment measures based on externally defined indicators from the Project-level Women’s Empowerment in Agriculture Index (pro-WEAI). The study design used mixed methods, with qualitative data collected through focus group discussions, life histories, and community profiles, and quantitative data collected through the pro-WEAI survey tool. Although Pro-WEAI results indicated that women and men in the study communities have achieved gender parity and experience a similar level of empowerment, qualitative findings suggest that experiences of empowerment don’t necessarily fit with Index scores. Rather, conceptualizations of empowerment by people of different ages and genders are highly diverse. Participants of all genders suggested that women’s empowerment is more limited than men’s, as women who are not. Subordinate to men risk being rejected or stigmatized by their communities. Qualitative findings suggest that empowered men are seen as “desirable” by their communities, whereas empowered women are “openly admired” and “treated as a threat/feared” in equal turn. Furthermore, results revealed that the under-involvement of men in empowerment initiatives has contributed to feelings of resentment and neglect. These findings suggest that capturing and accounting for multiple and diverse emic definitions of empowerment for different social groups, which lies beyond the scope of standardized quantitative measures, is essential to measuring and supporting empowerment in ways that are valuable and recognizable to the target group(s) of a given development initiative. Finally, results show that to support the effective empowerment of women and men, there is a need to include men, integrate safeguards for backlash against empowered women, and transform norms that hinder the acceptance of empowered women by their families and communities.